Spatial variations of each habitat factors. - Weifeng Gui (20861864) (2025)
(A) Spatial variation of accumulate temperature. (B) Spatial variation of mean temperature. (C) Spatial variation of attitude. (D) Spatial variation of annual precipitation. (E) Spatial variation of relevant humidity.